2016
DOI: 10.1111/mec.13879
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal gene expression in a migratory songbird

Abstract: The annual migration of a bird can involve thousands of kilometres of nonstop flight, requiring accurately timed seasonal changes in physiology and behaviour. Understanding the molecular mechanisms controlling this endogenous programme can provide functional and evolutionary insights into the circannual biological clock and the potential of migratory species to adapt to changing environments. Under naturally timed photoperiod conditions, we maintained captive Swainson's thrushes (Catharus ustulatus) and perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 88 publications
3
52
0
Order By: Relevance
“…Likewise, we expect that the interpretation of field data can be guided by growing insights into timing mechanisms gathered from captive studies. A particularly promising avenue are genetic approaches 5,116,141,[165][166][167][168][169] . These are increasingly used to identify mechanistic processes, specific features, and evolutionary consequences of migration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, we expect that the interpretation of field data can be guided by growing insights into timing mechanisms gathered from captive studies. A particularly promising avenue are genetic approaches 5,116,141,[165][166][167][168][169] . These are increasingly used to identify mechanistic processes, specific features, and evolutionary consequences of migration.…”
Section: Discussionmentioning
confidence: 99%
“…These are increasingly used to identify mechanistic processes, specific features, and evolutionary consequences of migration. For example, several recent studies compared gene expression, either globally or for candidate genes, between migrants and non-migrants, or between migrants during and outside migration phases 141,[165][166][167][168] . These studies give important leads to identifying the physiological organization of the timing of migration and the interactive roles of different physiological systems.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, there was an increased expression of genes associated with lipid transport and fatty acid catabolic processes in the muscle and with a ribosomal structure that indicated protein synthesis in the blood of the migrant ( J. h. hyemalis ) compared with the resident ( J. h. carolinensis ) juncos (Fudickar et al., ). Furthermore, Johnston, Paxton, Moore, Wayne, and Smith () performed RNA‐Seq of brain tissue, and found that genes involved in focal adhesion, proliferation and motility had higher expression during the migratory state than during the non‐migratory state in the ventral hypothalamus of captive Swainson's thrushes ( Catharus ustulatus ). In contrast, a study of the blood transcriptome on partial migratory European blackbirds ( Turdus merula ) reported only four differentially expressed genes that are possibly associated with the hyperphagia, moulting and enhanced DNA replication in blackbirds (Franchini et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Using comparative gene expression, we can get a better understanding of how the genome is regulated at different stages of bird migration (Box 2). Johnston et al (2016), using RNA-seq data, found 188 genes that were differentially expressed in the brain of captive Swainson's Thrushes Catharus ustulatus during different migratory states. A large number of these genes were associated with functions such as cell adhesion, proliferation and motility, and the authors hence suggested that migration-related changes might be regulated by seasonal neural plasticity (Johnston et al 2016).…”
Section: Migration Strategiesmentioning
confidence: 99%
“…Johnston et al (2016), using RNA-seq data, found 188 genes that were differentially expressed in the brain of captive Swainson's Thrushes Catharus ustulatus during different migratory states. A large number of these genes were associated with functions such as cell adhesion, proliferation and motility, and the authors hence suggested that migration-related changes might be regulated by seasonal neural plasticity (Johnston et al 2016). However, migration is a complex behaviour, which certainly involves hundreds of genes, some of them with known functions (these can be identified by annotation with other known genes) and others, for which a function still needs to be explored.…”
Section: Migration Strategiesmentioning
confidence: 99%